Depletion stabilization of emulsions based on bacterial cellulose/carboxymethyl chitosan complexes. (1st December 2022) - Zhang, Yamei; Yang, Shujuan; Tang, Haiyun; Wan, Sihui; Qin, Wenqi; Zeng, Qu; Huang, Junhao; Yu, Gaobo; Feng, Yuhong; Li, Jiacheng
Abstract: The regulation of the magnitude of the depletion effect is necessary for accurately predicting and explaining the emulsion stabilization mechanism. Herein, the bacterial cellulose/carboxymethyl chitosan (BC/CCS) complexes with tunable assembled behaviors were prepared and designed via electrostatic interaction. Specially, the emulsions stabilized by BC/CCS complexes exhibited excellent stability as compared with that stabilized by BC polymers alone. At pH 9.6, BC/CCS complexes in the continuous phase induced long-range depletion-stabilization effect to stabilize emulsions. Additionally, the magnitude of depletion effect of BC/CCS complexes could be improved by increasing BC concentration, and effectively stabilized emulsions. Furthermore, with the decrease to pH 7.0, the interfacial adsorption layers at the oil-water interface prevented oil droplets from agglomerating, but did not show better emulsion stability. These results clarified that the magnitude of the depletion effect could be controlled by altering BC-based complexes particles, which would be useful for the applications of emulsions in numerous fields. Graphical abstract: Unlabelled Image